2004
DOI: 10.4319/lo.2004.49.1.0117
|View full text |Cite
|
Sign up to set email alerts
|

Competition between biological and photochemical processes in the mineralization of dissolved organic carbon

Abstract: The photo-and bioreactive components of dissolved organic matter (DOM) from three different environments were determined during long-term decomposition experiments. Terrigenous DOM was collected from a black-water system, plankton DOM was harvested from phytoplankton cultures, and lake water served as a DOM source with both terrigenous and plankton components. Photomineralization accounted for the removal of 46 and 7% of terrigenous and lake-dissolved organic carbon (DOC), respectively, while no loss in DOC wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
244
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(271 citation statements)
references
References 35 publications
25
244
1
1
Order By: Relevance
“…While the concept of competing processes and DOC pools of mixed lability (Obernosterer and Benner 2004) has been proposed, previous experiments to determine the effect of photochemistry on microbial carbon lability are rarely quantitative with respect to total photon absorption by the sample, and studies of the spectral dependence of the response are rare (Miller and Moran 1997;Obernosterer and Benner 2004;Vahatalo and Wetzel 2004). Some studies have attempted to examine the transfer of DOC between photochemically and microbially labile pools, as well as estimate total pool size, by performing successive photodegradation and microbial degradation experiments (Obernosterer and Benner 2004;Vahatalo and Wetzel 2004). These experiments attempted to address the pool size while keeping in mind the fact that the biologically labile pool can also have photochemical activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While the concept of competing processes and DOC pools of mixed lability (Obernosterer and Benner 2004) has been proposed, previous experiments to determine the effect of photochemistry on microbial carbon lability are rarely quantitative with respect to total photon absorption by the sample, and studies of the spectral dependence of the response are rare (Miller and Moran 1997;Obernosterer and Benner 2004;Vahatalo and Wetzel 2004). Some studies have attempted to examine the transfer of DOC between photochemically and microbially labile pools, as well as estimate total pool size, by performing successive photodegradation and microbial degradation experiments (Obernosterer and Benner 2004;Vahatalo and Wetzel 2004). These experiments attempted to address the pool size while keeping in mind the fact that the biologically labile pool can also have photochemical activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Photodegraded DOM molecules are smaller and less aromatic, and therefore more labile and easily consumed by bacteria, than are the unaltered compounds in the initial DOM pool (Wetzel et al 1995;Moran and Zepp 1997;Bertilsson and Tranvik 1998;Obernosterer and Benner 2004). The presence of photodegraded and bioavailable DOM has been observed to fuel increases in BP in the short term, with these effects fading over longer observational periods.…”
Section: Photoreactivity Of Mackenzie River Freshet Dommentioning
confidence: 99%
“…Once present in the water column and exposed to sunlight, however, allochthonous DOM can be photodegraded via the absorption of high-energy ultraviolet (UV) wavelengths (280-400 nm). Absorbed UV breaks down aromatic carbon rings, producing smaller, less aromatic DOM molecules (Bertilsson and Tranvik 2000;Osburn et al 2001;Sulzberger and Durisch-Kaiser 2009) that have lower molecular weights and are more bioavailable for bacterial consumption and decomposition (Wetzel et al 1995;Moran and Zepp 1997;Bertilsson and Tranvik 1998;Obernosterer and Benner 2004). Heterotrophic grazers subsequently consume bacteria, which shunts otherwise unavailable carbon, organic matter, and energy back into the aquatic food web via the microbial loop (Azam et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Characterizing DOM degradation remains challenging, however, due to the complex nature of DOM, the variety of microbial metabolic pathways, and the various environmental conditions that regulate bacterial metabolism (Eichinger et al, 2011). Despite these challenges, much has been learned by tracking changes in DOC concentration and DOM composition during incubation experiments, including the variation in biomineralization rates as a function of DOM source (e.g., Moran and Zepp, 1997;Obernosterer and Benner, 2004), the relationship of microbial activity to the production of labile (e.g., Kawasaki and Benner, 2006) and refractory (e.g., Ogawa et al, 2001;Jiao et al, 2010;Lechtenfeld et al, 2015) DOM, and how bacterial-derived refractory material compares structurally to refractory DOM in the ocean (e.g., Osterholz et al, 2015). Studies using ultrahigh resolution mass spectrometry have revealed additional molecular-level transformations in DOM as a result of microorganism activity (Kujawinski et al, 2004), including a significant decrease in the molecular diversity of terrigenous DOM (Seidel et al, 2015) and a preferential degradation of oxygen-rich molecules on a time scale of several days (Kim et al, 2006;Medeiros et al, 2015c;Seidel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%